Modificación de parámetros de maquinado de un sistema cnc para evitar la aparición de chatter en un proceso de fresado (2021)
Regenerative chatter is a form of dynamic instability present in machining processes. This factor affects the efficiency of the cut, increases the wear of the tool, decreases the quality of the piece and presents abnormal noise during the process. This happens when the cutting force creates a displacement between the tool, which has an elastic nature, and the workpiece, causing an increase in the thickness of the chip, experiencing waves on its internal and external surfaces due to the vibrations present and past. This project presents a method for controlling the machining parameters of a CNC milling machine taking into account the lobe diagrams to determine the stability and chatter reduction.